Pemeriksaan dan Pengobatan Gratis Pasca Galodo di Nagari Paninggahan - Al-Ikhlas; Kadapi Hutabarat; Ahmad Razfadli Sabri; Pratiwi Zulus; Ermiyanti Ermiyanti (CV. ITTC INDONESIA, 2026)
Health is a crucial aspect that requires special attention after a natural disaster. The Galodo disaster that struck Paninggahan Village, Solok City, not only caused environmental and infrastructure damage, but also had the potential to cause various health problems for the affected community. Through the Community Service Program (KKN), students collaborated with the Indonesian Red Cross (PMI) to conduct free health checks and provide medicines to the Galodo-affected community. This activity aimed to detect community health conditions early, provide basic health services, and raise public awareness of the importance of maintaining health after a disaster. The results of the activity showed high enthusiasm from the community due to the easy access to fast and free health services. This program is expected to improve public health while strengthening the synergy between students, health workers, and the community in post-disaster recovery efforts.